A method for improving high temperature durability of K465 alloy

By optimizing the casting and heat treatment process of K465 alloy, microscopic loosening, grain size control and intergranular bonding force are eliminated, the problem of unstable high-temperature and durability performance of K465 alloy is solved, and the high-temperature durability performance is achieved significantly improved.

CN119747590APending Publication Date: 2025-04-04重庆三耐科技有限责任公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411882041.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The high-temperature and durability of existing K465 alloys is unstable and difficult to meet technical requirements.

Method used

By optimizing the casting process and heat treatment process, including increasing the gate cup size, increasing the amount of molten steel, changing the surface layer production materials, improving the test rod shape and preheating process, improving the melting and injection process and heat treatment process, eliminating the microscopic looseness of the test rod, controlling the grain size level, and improving the intergranular bonding force.

Benefits of technology

The microscopic loosening is controlled within 5%, the grain size is controlled at about 6 levels. The insulation section is added during the heat treatment process, ensuring that the thermal stress does not destroy the intergranular bonding force, improving the high-temperature and durable performance of K465 alloy, and meeting the technical requirements of lasting time ≥40 hours under 975℃ and 225MPa stresses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747590A_ABST
    Figure CN119747590A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of K465 alloy, and specifically relates to a method for improving the high-temperature durability of K465 alloy. The method comprises the following steps: S1: test rod casting; the diameter of the pouring cup is Φ90, the height is 100 mm, the surface layer is made of silica sol and white corundum powder; the sanding material is 80# white corundum sand; the test rod packing sand filling material is 60# white corundum sand, and the preheating temperature is 1100°C±20°C; S2: melting and pouring process; the refining temperature is 1600°C±10°C, and the pouring temperature is 1510°C±10°C; S3: heat treatment; after heating from entering the furnace to 950°C±10°C and keeping warm for 40±5 minutes, the temperature is then raised to a heat treatment temperature of 1210°C±10°C and kept warm. The invention adopts reasonable casting process and heat treatment process to eliminate the microporosity of the test rod, control the grain size grade, and improve the intercrystalline bonding force, so as to obtain higher high-temperature durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of K465 alloy, and in particular relates to a method for improving the high temperature endurance performance of K465 alloy. Background Art

[0002] K465 alloy is a high-performance high-temperature alloy with excellent high-temperature strength, creep resistance, thermal fatigue resistance and good corrosion resistance. It has been widely used in aerospace, energy, chemical industry and other fields.

[0003] At present, the manufacturing process of K465 alloy mainly includes: Melting: Use vacuum induction furnace to melt the master alloy to ensure the uniform and pure composition of the alloy. Casting: Pour the smelted master alloy into castings. Investment casting and other methods can be used to obtain castings with complex shapes and precise dimensions. Heat treatment: Heat treatment of castings to improve their mechanical properties and corrosion resistance. The heat treatment system is usually 1210℃±10℃ for 4 hours, air cooling or vacuum temperature control cooling. The alloy can also be used in the cast state. Processing: According to needs, the castings are machined, such as turning, milling, drilling, etc., to obtain the final shape and size of the parts. Surface treatment: Surface treatment of parts, such as aluminizing, vapor deposition, etc., to improve their surface hardness and corrosion resistance.

[0004] However, during the manufacturing process, the high-temperature endurance performance often fails to meet the technical requirements; in order to improve the high-temperature endurance performance of metals, corresponding optimization measures need to be taken. Summary of the invention

[0005] In order to solve the problem of stable high-temperature endurance performance of K465 cast high-temperature alloy in the prior art, the present invention provides a method for improving the high-temperature endurance performance of K465 alloy, adopting reasonable casting process and heat treatment process to eliminate the micro-looseness of the test rod, control the grain size grade, and improve the intercrystalline bonding force, so as to achieve the purpose of obtaining higher high-temperature endurance performance.

[0006] The present invention solves the technical problem by adopting the following technical solutions:

[0007] The present invention aims to provide a method for improving the high temperature durability of K465 alloy, comprising the following steps:

[0008] S1: Test rod casting; the pouring cup diameter is Φ90, the height is 100mm, the surface layer is made of silica sol and white corundum powder; the sanding material is 80# white corundum sand; the test rod packing sand filling material is 60# white corundum sand, and the preheating temperature is 1100℃±20℃;

[0009] S2: Melt injection process; refining temperature is 1600℃±10℃, pouring temperature is 1510℃±10℃;

[0010] S3: Heat treatment: raise the temperature to 950℃±10℃ from the time of entering the furnace and keep it warm for 40±5 minutes, then raise the temperature to the heat treatment temperature of 1210℃±10℃ and keep it warm.

[0011] Furthermore, a formed test bar wax mold is used in the test bar casting, with a combination of 8 pieces / group; and a molten steel volume of 8.0 kg.

[0012] Furthermore, the test rod packing method is: after laying a layer of 60# white corundum sand with a thickness of 20-30mm on the bottom of the sand box, the test rod mold shell is placed in the middle of the sand box; then the gap between the mold shell and the sand box is filled with 60# white corundum sand, and the filling is continued to be 35-45mm from the upper part of the pouring cup.

[0013] Furthermore, the packing tooling: the sand box is made of 2.5mm heat-resistant steel plate by bending, cutting and welding; the diameter is 250mm and the height is 300mm.

[0014] Furthermore, the melting and pouring process is as follows: use a vacuum induction furnace to melt the master alloy rod, and before starting melting, refining and pouring, the vacuum degree in the furnace is reduced to below 5Pa; when the refining temperature reaches 1600℃±10℃, start timing; the refining time is controlled at 12-15 minutes; after refining, the molten steel temperature is reduced to the pouring temperature and pouring is carried out immediately, and the pouring speed is controlled at 2-3 seconds.

[0015] Furthermore, the time from the start of shell transfer to the end of pouring is controlled within 3 minutes; after pouring, the vacuum degree is maintained below 10Pa, and the furnace door is opened to take out the shell after the time is greater than 5 minutes.

[0016] Furthermore, the furnace is loaded before heat treatment: the test bars are placed flat on the tray and fixed with high-temperature alloy blocks, and a gap of 5-15 mm is maintained between the test bars.

[0017] Furthermore, the heat treatment method is: when the vacuum degree is less than 1Pa, start heating to 950°C and keep it warm for 35-45 minutes; continue heating to the insulation temperature, keep it warm for 4 hours, then cool it with argon, stop filling with argon, and then cool it naturally to room temperature.

[0018] Furthermore, the argon gas cooling method is: the cooling rate from 1210 to 1000°C is controlled at 40±15°C, and after reaching 1000°C, cooling is performed at a speed equivalent to air cooling, and the cooling time is 35-45 minutes.

[0019] In order to improve the high temperature durability of K465 alloy, the present invention mainly makes the following improvements compared with the prior art.

[0020] Step 1: Increase the size of the pouring cup and the amount of molten steel to eliminate the micro-porosity of the test rod.

[0021] 1. Existing combination scheme: using forming test rod wax mold, forming pouring system, combination: 8 pieces / group. The amount of molten steel is 6.0kg. Figure 1 shown.

[0022] 2. Combination scheme of the present invention: replace the pouring cup of the molding pouring system with a large pouring cup (diameter changed from Φ60 to Φ90, height changed from 60mm to 100mm); use the molding test rod wax mold, combination: 8 pieces / group. The amount of molten steel is increased to 8.0kg. Figure 2 shown.

[0023] Step 2: Replace the surface layer material to create conditions for obtaining coarse crystals.

[0024] 1. Existing layer making materials: silica sol (830) + zircon powder (320 mesh) + cobalt aluminate powder; sand spreading material: 80-100 mesh zircon sand.

[0025] Shell making process:

[0026]

[0027] 2. The surface layer of the present invention is made of materials: silica sol (830) + white corundum powder (320 mesh); sanding material: 80# white corundum sand.

[0028] Shell making process:

[0029]

[0030] Step 3: Improve the test rod shape and preheating process to improve the thermal insulation effect and increase the grain growth momentum.

[0031] 1. The existing test rod packing sand filling material is 24# bauxite sand, and the preheating temperature is 980℃±20℃.

[0032] Packing tooling: The sand box is made of 2.5mm heat-resistant steel plate, which is bent, cut and welded; the diameter is 250mm and the height is 300mm.

[0033] Packing: After laying a layer of 24# bauxite sand (30-40mm thick) on the bottom of the sand box, place the test rod mold shell in the middle of the sand box; then fill the gap between the mold shell and the sand box with 24# bauxite sand, and continue to fill it to about 60mm from the top of the pouring cup, and gently shake the sand box to make the sand have a certain degree of compactness.

[0034] Pre-firing: The finished shell is sent into a gas-fired baking furnace and heated to 980°C, kept warm for more than 4 hours, and then poured.

[0035] 2. The sand filling material for the test rod packing of the present invention is 60# white corundum sand, and the preheating temperature is 1100℃±20℃.

[0036] Packing tooling: The sand box is made of 2.5mm heat-resistant steel plate, which is bent, cut and welded; the diameter is 250mm and the height is 300mm.

[0037] Packing: After laying a layer of 60# white corundum sand (20-30mm thick) on the bottom of the sand box, place the test rod mold shell in the middle of the sand box; then fill the gap between the mold shell and the sand box with 60# white corundum sand, and continue to fill it to about 40mm from the top of the pouring cup, and gently shake the sand box to make the sand have a certain degree of compactness.

[0038] Pre-firing: The finished shell is sent into a gas-fired baking furnace and heated to 1100°C, kept warm for more than 3 hours, and then poured.

[0039] Step 5: Improve the melting process, increase the refining temperature to make the alloying more complete, and increase the pouring temperature to make it easier to obtain coarse grains.

[0040] 1. Existing melt-casting process: refining temperature is 1550℃±10℃, pouring temperature is 1430℃±10℃.

[0041] Use a vacuum induction furnace to melt the master alloy rods. Before melting, refining and pouring, the vacuum degree in the furnace is required to drop to below 5Pa. When the refining temperature reaches 1550℃±10℃, start timing, and control the refining time to 10-12 minutes. After refining, reduce the temperature of the molten steel to the pouring temperature and pour immediately, and control the pouring speed to 2-3 seconds. Note: From the start of shell transfer to the end of pouring, the time is controlled within 6 minutes; after pouring, the vacuum degree is kept below 30Pa, and the furnace door is opened to take out the shell after more than 5 minutes.

[0042] 2. Current melt-casting process: refining temperature is 1600℃±10℃, pouring temperature is 1510℃±10℃.

[0043] Use a vacuum induction furnace to melt the master alloy rods. Before melting, refining and pouring, the vacuum degree in the furnace is required to drop to below 5Pa. When the refining temperature reaches 1600℃±10℃, start timing; the refining time is controlled at 12-15 minutes. After refining, the molten steel temperature is lowered to the pouring temperature and pouring is carried out immediately, and the pouring speed is controlled at 2-3 seconds. Note: From the start of shell transfer to the end of pouring, the time is controlled within 3 minutes; after pouring, the vacuum degree is kept below 10Pa, and the furnace door is opened to take out the shell after more than 5 minutes.

[0044] Step 6: After pouring, cool for more than 10 hours, and after shelling, cutting, sand blasting, corrosion and inspection, obtain qualified test rod blanks and then transfer to heat treatment.

[0045] Step 7: Improve the heat treatment process to eliminate the thermal stress generated during the heating process.

[0046] 1. Existing process: directly raise the temperature from entering the furnace to 1210℃±10℃ for heat treatment and keep warm.

[0047] Test rods and products are processed in the same furnace

[0048] Furnace loading: Place the test bars flat on the tray and fix them with high-temperature alloy blocks, keeping a gap of 5-15mm between the test bars.

[0049] When the vacuum degree is less than 1Pa, start heating to the holding temperature, keep warm for 4 hours, then cool with argon (the cooling rate from 1210 to 1000°C is controlled at 40±15°C, and after reaching 1000°C, cool at a rate equivalent to air cooling, and the cooling time is about 40 minutes), stop filling with argon, and then cool naturally to room temperature.

[0050] 2. The process of the present invention: the temperature is raised to 950°C ± 10°C from the time of entering the furnace and kept warm for 40 ± 5 minutes, and then the temperature is raised to the heat treatment temperature of 1210°C ± 10°C and kept warm.

[0051] Test rods and products are processed in the same furnace

[0052] Furnace loading: Place the test bars flat on the tray and fix them with high-temperature alloy blocks, keeping a gap of 5-15mm between the test bars.

[0053] When the vacuum degree is less than 1Pa, start heating to 950℃ and keep it warm for about 40 minutes; continue heating to the insulation temperature, keep it warm for 4 hours, then cool it with argon (the cooling rate from 1210-1000℃ is controlled at 40±15℃, and after reaching 1000℃, cool it at a rate equivalent to air cooling, and the cooling time is about 40 minutes), stop filling with argon, and then cool it naturally to room temperature.

[0054] Compared with the prior art, the beneficial technical effects of the present invention are:

[0055] The invention designs a new test rod casting process and heat treatment process, which mainly include 1. increasing the size of the pouring cup and the amount of molten steel; 2. replacing the preparation material of the surface coating; 3. improving the test rod modeling and preheating process; 4. improving the melting and pouring process; 5. improving the heat treatment process. Through the above improvements, the micro-looseness of the test rod is eliminated, the grain size grade is controlled, and the intercrystalline bonding force is improved, thereby improving the high-temperature durability of the K465 alloy.

[0056] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above contents of the present invention and its objectives, features and advantages more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 It is a schematic diagram of the molding test rod wax mold and the molding pouring system in the existing combination scheme.

[0058] Figure 2 It is a schematic diagram of the molding test rod wax mold and the molding pouring system in the combination scheme of the present invention. DETAILED DESCRIPTION

[0059] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0060] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0061] Example 1

[0062] S1: Trial Bar Casting

[0063] The pouring cup of the molding pouring system is a large pouring cup with a diameter of Φ90 and a height of 100mm. The molding test rod wax mold is used, and the combination is 8 pieces / set. The amount of molten steel is 8.0kg.

[0064] Surface layer material: silica sol (830) + white corundum powder (320 mesh); sanding material: 80# white corundum sand.

[0065] Shell making process:

[0066]

[0067] Packing tooling: The sand box is made of 2.5mm heat-resistant steel plate, which is bent, cut and welded; the diameter is 250mm and the height is 300mm.

[0068] Packing: After laying a layer of 60# white corundum sand (25mm thick) on the bottom of the sand box, place the test rod mold shell in the middle of the sand box; then fill the gap between the mold shell and the sand box with 60# white corundum sand, and continue to fill it to 40mm from the top of the pouring cup, and gently shake the sand box to make the sand have a certain degree of compactness.

[0069] Pre-firing: The finished shell is sent into a gas-fired baking furnace and heated to 1100°C, kept warm for 5 hours, and then poured.

[0070] S2: Melt injection process

[0071] Use a vacuum induction furnace to melt the master alloy bar. Before melting, refining and pouring, the vacuum degree in the furnace is required to drop to 3Pa. When the refining temperature reaches 1600℃, start timing; the refining time is controlled at 13 minutes. After refining, the molten steel temperature is lowered to the pouring temperature and pouring is carried out immediately, and the pouring speed is controlled at 2 seconds. Note: From the start of shell transfer to the end of pouring, the time is controlled at 2 minutes; after pouring, the vacuum degree is maintained at 6Pa, and the furnace door is opened to take out the shell after 8 minutes.

[0072] After pouring, the casting is cooled for 13 hours, and after shelling, cutting, sand blasting, corrosion and inspection, the qualified test bar blank is obtained and then transferred to heat treatment.

[0073] S3: Heat treatment

[0074] The test bars are processed in the same furnace as the products;

[0075] Furnace loading: Place the test bars flat on the tray and fix them with high-temperature alloy blocks, keeping a 10mm gap between the test bars.

[0076] When the vacuum degree is 0.6Pa, heating is started to rise to 950°C and kept warm for 40 minutes; the temperature is continued to rise to the holding temperature, and after keeping warm for 4 hours, argon is filled for cooling (the cooling rate from 1210 to 1000°C is controlled at 40°C, and after reaching 1000°C, it is cooled at a rate equivalent to air cooling, and the cooling time is 40 minutes), argon filling is stopped, and then it is naturally cooled to room temperature.

[0077] Example 2

[0078] S1: Trial Bar Casting

[0079] The pouring cup of the molding pouring system is a large pouring cup with a diameter of Φ90 and a height of 100mm. The molding test rod wax mold is used, and the combination is 8 pieces / set. The amount of molten steel is 8.0kg.

[0080] Surface layer material: silica sol (830) + white corundum powder (320 mesh); sanding material: 80# white corundum sand.

[0081] Shell making process:

[0082]

[0083] Packing tooling: The sand box is made of 2.5mm heat-resistant steel plate, which is bent, cut and welded; the diameter is 250mm and the height is 300mm.

[0084] Packing: After laying a layer of 60# white corundum sand (20mm thick) on the bottom of the sand box, place the test rod mold shell in the middle of the sand box; then fill the gap between the mold shell and the sand box with 60# white corundum sand, and continue to fill it to 35mm from the top of the pouring cup, and gently shake the sand box to make the sand have a certain degree of compactness.

[0085] Pre-firing: The finished shell is sent into a gas-fired baking furnace and heated to 1080°C, kept warm for 8 hours, and then poured.

[0086] S2: Melt injection process

[0087] Use a vacuum induction furnace to melt the master alloy bar. Before melting, refining and pouring, the vacuum degree in the furnace is required to drop to 1Pa. When the refining temperature reaches 1590℃, start timing; the refining time is controlled at 12 minutes. After refining, the molten steel temperature is lowered to the pouring temperature and pouring is carried out immediately, and the pouring speed is controlled at 3 seconds. Note: From the start of shell transfer to the end of pouring, the time is controlled at 2min; after pouring, the vacuum degree is maintained at 6Pa, and the furnace door is opened to take out the shell after 8min.

[0088] After pouring, it is cooled for 15 hours, and after shelling, cutting, sand blasting, corrosion and inspection, the qualified test bar blank is obtained and then transferred to heat treatment.

[0089] S3: Heat treatment

[0090] The test bars are processed in the same furnace as the products;

[0091] Furnace loading: Place the test bars flat on the tray and fix them with high-temperature alloy blocks, keeping a 5mm gap between the test bars.

[0092] When the vacuum degree was 0.4Pa, heating was started to rise to 950°C and kept warm for 35 minutes; the temperature was continued to rise to the holding temperature, kept warm for 4 hours, and then cooled with argon gas (the cooling rate from 1210 to 1000°C was controlled at 25°C, and after reaching 1000°C, it was cooled at a rate equivalent to air cooling, and the cooling time was 25 minutes), the argon gas filling was stopped, and then naturally cooled to room temperature.

[0093] Example 3

[0094] S1: Trial Bar Casting

[0095] The pouring cup of the molding pouring system is a large pouring cup with a diameter of Φ90 and a height of 100mm. The molding test rod wax mold is used, and the combination is 8 pieces / set. The amount of molten steel is 8.0kg.

[0096] Surface layer material: silica sol (830) + white corundum powder (320 mesh); sanding material: 80# white corundum sand.

[0097] Shell making process:

[0098]

[0099] Packing tooling: The sand box is made of 2.5mm heat-resistant steel plate, which is bent, cut and welded; the diameter is 250mm and the height is 300mm.

[0100] Packing: After laying a layer of 60# white corundum sand (30mm thick) on the bottom of the sand box, place the test rod mold shell in the middle of the sand box; then fill the gap between the mold shell and the sand box with 60# white corundum sand, and continue to fill it to 45mm from the top of the pouring cup, and gently shake the sand box to make the sand have a certain degree of compactness.

[0101] Pre-firing: The molded shell is sent into a gas-fired baking furnace and heated to 1120°C, kept warm for 6 hours, and then poured.

[0102] S2: Melt injection process

[0103] Use a vacuum induction furnace to melt the master alloy bar. Before melting, refining and pouring, the vacuum degree in the furnace is required to drop to 4Pa. When the refining temperature reaches 1610℃, start timing; the refining time is controlled at 15 minutes. After refining, the molten steel temperature is lowered to the pouring temperature and pouring is carried out immediately, and the pouring speed is controlled at 2 seconds. Note: From the start of shell transfer to the end of pouring, the time is controlled at 1min; after pouring, the vacuum degree is maintained at 3Pa, and the furnace door is opened to take out the shell after 10min.

[0104] After pouring, it is cooled for 16 hours, and after shelling, cutting, sand blasting, corrosion and inspection, the qualified test bar blank is obtained and then transferred to heat treatment.

[0105] S3: Heat treatment

[0106] The test bars are processed in the same furnace as the products;

[0107] Furnace loading: Place the test bars flat on the tray and fix them with high-temperature alloy blocks, keeping a 15mm gap between the test bars.

[0108] When the vacuum degree is less than 0.8Pa, start heating to 950℃ and keep it warm for 45 minutes; continue heating to the insulation temperature, keep it warm for 4 hours, then cool it with argon (the cooling rate from 1210-1000℃ is controlled at 55℃, and after reaching 1000℃, cool it at a rate equivalent to air cooling, and the cooling time is 45 minutes), stop filling with argon, and then cool it naturally to room temperature.

[0109] Comparative Example 1

[0110] The pouring cup of the molding pouring system has a diameter of Φ60 and a height of 60mm. The molding test rod wax mold and molding pouring system are used, and the combination is 8 pieces / set. The amount of molten steel is 6.0kg.

[0111] Original surface layer making materials: silica sol (830) + zircon powder (320 mesh) + cobalt aluminate powder; sand spreading material: 80-100 mesh zircon sand.

[0112] Shell making process:

[0113]

[0114]

[0115] Packing tooling: The sand box is made of 2.5mm heat-resistant steel plate, which is bent, cut and welded; the diameter is 250mm and the height is 300mm.

[0116] Packing: After laying a layer of 24# bauxite sand (35mm thick) on the bottom of the sand box, place the test rod mold shell in the middle of the sand box; then fill the gap between the mold shell and the sand box with 24# bauxite sand, and continue filling it to 60mm from the top of the pouring cup, and gently shake the sand box to make the sand have a certain degree of compactness.

[0117] Pre-firing: The finished shell is sent into a gas-fired baking furnace and heated to 980°C, kept warm for 5 hours, and then poured.

[0118] Melt injection process: refining temperature is 1550℃±10℃, pouring temperature is 1430℃±10℃.

[0119] Use a vacuum induction furnace to melt the master alloy rods. Before melting, refining and pouring, the vacuum degree in the furnace is required to drop to 3Pa. When the refining temperature reaches 1550℃, start timing, and the refining time is controlled at 11 minutes. After refining, the molten steel temperature is lowered to the pouring temperature and pouring is carried out immediately, and the pouring speed is controlled at 2 seconds. Note: From the start of shell transfer to the end of pouring, the time is controlled within 2 minutes; after pouring, the vacuum degree is kept below 6Pa, and the furnace door is opened to take out the shell after 8 minutes.

[0120] After pouring, the casting is cooled for 13 hours, and after shelling, cutting, sand blasting, corrosion and inspection, the qualified test bar blank is obtained and then transferred to heat treatment.

[0121] Test rods and products are processed in the same furnace

[0122] Furnace loading: Place the test bars flat on the tray and fix them with high-temperature alloy blocks, keeping a 10mm gap between the test bars.

[0123] When the vacuum degree was 0.6Pa, heating was started to rise to the holding temperature. After holding for 4 hours, cooling was performed with argon gas (the cooling rate from 1210 to 1000°C was controlled at 40°C, and after reaching 1000°C, cooling was performed at a rate equivalent to air cooling, and the cooling time was 40 minutes). The argon gas filling was stopped, and then the sample was naturally cooled to room temperature.

[0124] The microporosity of the test rod manufactured by the process of the present invention can be controlled within 5%; the grain size can be controlled at about level 6; by adding a heat preservation section during the heat treatment process, it is ensured that the thermal stress does not destroy the bonding force between the grains. After multiple verifications and productions, the high-temperature endurance performance is stable, and the endurance time is ≥40h at 975℃ and 225MPa stress, which can fully meet the technical requirements.

[0125] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.

[0126] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for improving the high temperature durability of K465 alloy, characterized in that: The following steps are involved: S1: Test rod casting; the pouring cup diameter is Φ90, the height is 100mm, the surface layer is made of silica sol and white corundum powder; the sanding material is 80# white corundum sand; the test rod packing sand filling material is 60# white corundum sand, and the preheating temperature is 1100℃±20℃; S2: Melt injection process; refining temperature is 1600℃±10℃, pouring temperature is 1510℃±10℃; S3: Heat treatment: raise the temperature to 950℃±10℃ from the time of entering the furnace and keep it warm for 40±5 minutes, then raise the temperature to the heat treatment temperature of 1210℃±10℃ and keep it warm.

2. A method for improving the high temperature durability of K465 alloy as claimed in claim 1, characterized in that: The test bar casting uses a formed test bar wax mold, combination: 8 pieces / group; the molten steel volume is 8.0kg.

3. A method for improving the high temperature durability of K465 alloy as claimed in claim 2, characterized in that: The test rod packing method is: after laying a layer of 60# white corundum sand with a thickness of 20-30mm on the bottom of the sand box, place the test rod mold shell in the middle of the sand box; then fill the gap between the mold shell and the sand box with 60# white corundum sand, and continue to fill it to 35-45mm from the top of the pouring cup.

4. A method for improving the high temperature durability of K465 alloy as claimed in claim 3, characterized in that: Packing tooling: The sand box is made of 2.5mm heat-resistant steel plate, which is bent, cut and welded; the diameter is 250mm and the height is 300mm.

5. A method for improving the high temperature durability of K465 alloy as claimed in claim 1, characterized in that: The melting and pouring process is as follows: use a vacuum induction furnace to melt the master alloy rods. Before starting melting, refining and pouring, the vacuum degree in the furnace is reduced to below 5Pa; when the refining temperature reaches 1600℃±10℃, start timing; the refining time is controlled at 12-15 minutes; after refining, the molten steel temperature is reduced to the pouring temperature and pouring is carried out immediately, and the pouring speed is controlled at 2-3 seconds.

6. A method for improving the high temperature durability of K465 alloy as claimed in claim 5, characterized in that: The time from the transfer of the mold shell to the end of pouring is controlled within 3 minutes; after pouring, the vacuum degree is kept below 10Pa, and the furnace door is opened to take out the mold shell after more than 5 minutes.

7. A method for improving the high temperature durability of K465 alloy as claimed in claim 1, characterized in that: Loading the furnace before heat treatment: Place the test bars flat on the tray and fix them with high-temperature alloy blocks, keeping a gap of 5-15mm between the test bars.

8. A method for improving the high temperature durability of K465 alloy as claimed in claim 7, characterized in that: The heat treatment method is: when the vacuum degree is less than 1Pa, start heating to 950°C and keep it warm for 35-45 minutes; continue heating to the insulation temperature, keep it warm for 4 hours, then cool it with argon, stop filling with argon, and then cool it naturally to room temperature.

9. A method for improving the high temperature durability of K465 alloy as claimed in claim 8, characterized in that: The argon gas cooling method is: the cooling rate from 1210 to 1000°C is controlled at 40±15°C, and after reaching 1000°C, cooling is carried out at the air cooling rate, and the cooling time is 35-45 minutes.

Citation Information

Cited By

  • K465 high-temperature alloy and preparation method thereof

    CN120924829A

  • Preparation device and preparation method for ultra-pure high-temperature alloy test bar

    CN121945705A